SUICIDAL BEHAVIOR ON PREVENTION OF ATVOR PSYCHOPROPHYPHYLACTIC MEASURES WITH ADOLESCENTS - Raziqova Lola Tuychiyevna (Journals Park Publishing, 2022)
This article describes psycho-prophylactic measures to prevent suicidal behavior with adolescents and how to organize psycho-preventive work.
Keywords: suicidal behavior; deviant; pedagogical-psychological condition